GOALS OF A MILITARY LEADER TRAINING TO EXECUTE HIS PEDAGOGICAL FUNCTIONS - Kucheriavyi, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
Training of cadets as prospective military leaders at a military educational institution faces the problem of absence of its intelligibly determined goals. Search for solution of this problem in the aspect of pedagogical functions execution by a military leader is the central objective of the research. The other one is to characterize actual conditions which provide realization of determined goals of leader training at a Ukrainian military educational institution. Results of the previous researches analysis demonstrate the necessity of leader pedagogical training on the one hand and the lack of special pedagogical courses in curriculums of many military educational institutions on the other hand. Description of a military leader activity, which is present in the references to foreign research works, clearly points to execution of the pedagogical function by an officer. For example, a military leader is responsible for the professional development of soldiers, their training and informing, regarding the need for and purpose of the military discipline, their duties etc. The content of pedagogical function execution by military leader is determined in the article. It consists from individual and group training and upbringing soldiers, self-study and self-upbringing. The goals a military leader training are presented as a complex of special knowledge and skills which are necessary for execution of pedagogical function. They are determined particularly for stages of training or upbringing action: preparing, execution and self-assessment of pedagogical activity based on results of an action. The knowledge and skills that correspond to the process of formation of military unit cohesion are determined from the complex of knowledge and skills related to upbringing. And this direction of military leader’s activity is emphasized, due to it’s significant importance. Knowledge and skills of self-study and self-upbringing are viewed in the separate block. Groups of both explicitly pedagogical knowledge and skills and other ones with psychological and communicative nature are considered. Actual conditions for defined training goals implementation at a higher military educational institution are studied by way of example of Military Institute of Taras Shevchenko National University of Kyiv. It is remarked that cadets of Politology and Psychology specialities have sufficient pedagogical training, but cadets of other specialities gain knowledge that lack significant pedagogical content. So, they have no pedagogical practicum. The list of academic disciplines helpful for a military leader is proposed. It includes extensive pedagogical aspects for this in view.